2015
DOI: 10.5781/jwj.2015.33.5.26
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Life of the Repair TIG Welded Hastelloy X Superalloy

Abstract: Hastelloy X in this study was applied in jet engine F-15 air fighter as shroud to isolate the engine from outer skin. After 15 years operation at elevated temperature the mechanical properties decreased gradually due to the precipitation of continues second phases in the grain boundaries and precipitated inside the grain. The crack happened at the edge of the shroud due to the thermal and mechanical stress from jet engine. Selective TEM analysis found that the grain boundaries consist of M 23 C 6 carbide, M 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…38 Sihotang et al. 39 reported that the P precipitate is observed around the M 6 C phases. The absence of microsegregation in the GTA and PCGTA weldment at the WI is because of the higher rate of cooling rate with a steeper thermal gradient as compared to the WC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Sihotang et al. 39 reported that the P precipitate is observed around the M 6 C phases. The absence of microsegregation in the GTA and PCGTA weldment at the WI is because of the higher rate of cooling rate with a steeper thermal gradient as compared to the WC.…”
Section: Resultsmentioning
confidence: 99%
“…A similar observation was also reported on Alloy X by another investigator. 38 Sihotang et al 39 reported that the P precipitate is observed around the M 6 C phases. The absence of microsegregation in the GTA and PCGTA Figure 8.…”
Section: Sem/eds Observationmentioning
confidence: 99%